Using action research to explore the role of the international academic consultant: drawing on participants' perceptions in a teacher development project in Pakistan. Issue 1 (1st January 2018) - Hargreaves, Eleanore
Abstract: This paper problematises the involvement of the UK academic consultant in professional development projects among teachers in a developing, low-income nation. The context for this exploration was a four-year project in Pakistan in which I gave input as a UK consultant. My over-arching research question was: What was the value of my work as international academic consultant in providing professional development for teaching and learning in Pakistan? I gained insights into the issue through asking participants their perceptions, reflecting on these, acting on insights and then asking more questions in a continuous cycle of action and reflection. Participants in this case were head teachers and senior teachers from a range of private schools in Pakistan, including some of the wealthiest school chains. My findings were that participants did value the presence of the international consultant because they believed s/he had access to more valuable knowledge than local experts in many respects. However, participants valued the chance for activities and dialogue among their professional compatriots most of all.